Clinical application of a multiplex genetic pathogen detection system remaps the aetiology of diarrhoeal infections in Shanghai - Shiwen Wang; Feng Yang; Dong Li; Juanxiu Qin; Weiwei Hou; Lian Jiang; Mimi Kong; Yong Wu; Yuchen Zhang; Fuju Zhao; Yi Fang; Yingxin Miao; et al. (Gut Pathogens, 2018)
Abstract Background Culture-based diagnostic methods cannot achieve rapid and precise diagnoses for the identification of multiple diarrhoeal pathogens (DPs). A high-throughput multiplex genetic detection system (HMGS) was adapted and evaluated for the simultaneous identification and differentiation of infectious DPs and a broad analysis of DP infection aetiology. Results DP-HMGS was highly sensitive and specific for DP detection compared with culture-based techniques and was similar to singleplex real-time PCR. The uniform level of sensitivity of DP-HMGS for all DPs allowed us to remap the aetiology of acute diarrhoeal infections in Shanghai, correcting incidences of massively underdiagnosed DP species with accuracy approaching that of sequencing-based methods. The most frequent DPs were enteropathogenic Escherichia coli, rotavirus and Campylobacter jejuni. DP-HMGS detected two additional causes of infectious diarrhoea that were previously missed by routine culture-based methods: enterohemorrhagic E. coli and Yersinia enterocolitica. We demonstrated the age dependence of specific DP distributions, especially the distributions of rotavirus, intestinal adenovirus and Clostridium difficile in paediatric patients as well as those of dominant bacterial infections in adults, with a distinct “top 3” pattern for each age group. Finally, the multiplexing capability and high sensitivity of DP-HMGS allowed the detection of infections co-induced by multiple pathogens (approximately 1/3 of the cases), with some DPs preferentially co-occurring as infectious agents. Conclusions DP-HMGS has been shown to be a rapid, specific, sensitive and appropriate method for the simultaneous screening/detection of polymicrobial DP infections in faecal specimens. Widespread use of DP-HMGS is likely to advance routine diagnostic and clinical studies on the aetiology of acute diarrhoea.